2022
DOI: 10.3390/ma15093347
|View full text |Cite
|
Sign up to set email alerts
|

GIPAW Pseudopotentials of d Elements for Solid-State NMR

Abstract: Computational methods are increasingly used to support interpreting, assigning and predicting the solid-state nuclear resonance magnetic spectra of materials. Currently, density functional theory is seen to achieve a good balance between efficiency and accuracy in solid-state chemistry. To be specific, density functional theory allows the assignment of signals in nuclear resonance magnetic spectra to specific sites and can help identify overlapped or missing signals from experimental nuclear resonance magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The Perdew-Burke-Ernzerhof exchange-correlation functional has been adopted [39]. Normconserving Trouiller-Martins pseudopotentials with gauge including projector augmented wave (GIPAW) reconstruction are used [40,41] and the Kohn-Sham wavefunctions are expanded in a basis of plane waves up to a cutoff energy of 80 Ry. The Γ point was used for sampling the Brillouin zone [42].…”
Section: Theoretical Methodology and Modeling Detailsmentioning
confidence: 99%
“…The Perdew-Burke-Ernzerhof exchange-correlation functional has been adopted [39]. Normconserving Trouiller-Martins pseudopotentials with gauge including projector augmented wave (GIPAW) reconstruction are used [40,41] and the Kohn-Sham wavefunctions are expanded in a basis of plane waves up to a cutoff energy of 80 Ry. The Γ point was used for sampling the Brillouin zone [42].…”
Section: Theoretical Methodology and Modeling Detailsmentioning
confidence: 99%
“…Stepanov et al 143 applied DFT calculations to predict 13 C NMR chemical shifts of selected hydrocarbons adsorbed on Zn-modified zeolites. Ceresoli et al 144 reported on GIPAW pseudopotentials of d-elements for solid-state NMR. Hartman and Harper 145 improved the accuracy of GIPAW chemical shielding calculations with cluster and fragment corrections.…”
Section: Nuclear Shielding Calculation In Natural Productsmentioning
confidence: 99%
“…All fractional atomic coordinates were allowed to relax in P 1 symmetry using pseudopotentials of the kjpaw‐type from the pslibrary (version 1.0) [39] . For the gipaw calculations a single‐point SCF calculation were performed with norm‐conserving Troullier‐Martins type pseudopotentials [40] with PAW reconstruction [41] (X.pbe‐tm‐new‐gipaw‐dc.UPF files (X=P, O); Ca.pbe‐tm‐new‐dc.UPF) [42] . The PBE density functional [43,44] was used and if applicable (see below) non‐empirical van der Waals correction (vdW‐DF [45–48] ).…”
Section: Experimental Partmentioning
confidence: 99%
“…[39] For the gipaw calculations a single-point SCF calculation were performed with norm-conserving Troullier-Martins type pseudopotentials [40] with PAW reconstruction [41] (X.pbe-tm-new-gipaw-dc.UPF files (X=P, O); Ca.pbe-tm-new-dc.UPF). [42] The PBE density functional [43,44] was used and if applicable (see below) non-empirical van der Waals correction (vdW-DF [45][46][47][48] ). The convergence threshold for selfconsistency of the electronic wave function was set to 10 À 13 a.u., while the thresholds for the total energy and the atomic forces were set to 10 À 12 a.u.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%